2012
DOI: 10.1536/ihj.53.205
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pancreatic Cancer After Heart Transplantation

Abstract: SummaryMalignancy is not uncommon with immunosuppressive therapy, but pancreatic cancer is infrequently complicated in recipients of heart transplantation. Here we report a transplant case diagnosed with pancreatic cancer 4 years and 8 months after the heart transplantation. We changed the immunosuppressive regimen after the malignancy was detected, and administered everolimus along with chemotherapy using S-1, an oral fluoropyrimidine prodrug. The patient lived for 8 months after the diagnosis, and received m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The new immunosuppressant EVL, which is a mammalian target of rapamycin, has recently been demonstrated to have various advantages in terms of its prophylactic effect of CMV infection, 8,13) suppressive effect of cardiac allograft vasculopathy, [14][15][16] anti-malignancy effect, 17,18) and maintenance of renal function, 19) and subsequently its use has increased around the world. Although EVL has been reported to have a prophylactic effect towards PTLD, 18) it may not necessarily protect the development of early-PTLD completely considering the findings in the present patient.…”
Section: Discussionmentioning
confidence: 99%
“…The new immunosuppressant EVL, which is a mammalian target of rapamycin, has recently been demonstrated to have various advantages in terms of its prophylactic effect of CMV infection, 8,13) suppressive effect of cardiac allograft vasculopathy, [14][15][16] anti-malignancy effect, 17,18) and maintenance of renal function, 19) and subsequently its use has increased around the world. Although EVL has been reported to have a prophylactic effect towards PTLD, 18) it may not necessarily protect the development of early-PTLD completely considering the findings in the present patient.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] Recent clinical studies including ours also demonstrated the suppressive effects of EVL in cardiac allograft vasculopathy and post-transplant malignancy. [21][22][23][24][25] Considering that both SRL and EVL are mTOR inhibitors, EVL may also have a repressive effect on LVM. We here analyzed the relationship between EVL and LVM regression in Japanese HTx recipients.…”
Section: Eft Ventricular Hypertrophy (Lvh) Is Observed In Pa-mentioning
confidence: 99%